2010
DOI: 10.1088/0957-4484/21/16/165503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas sensing properties of PdO thin films with nano-sized cracks

Abstract: We report on a novel method for the fabrication of highly sensitive hydrogen gas sensors based on palladium oxide thin films and have investigated their hydrogen sensing properties and nanostructures. To our knowledge, this is the first report on the use of palladium oxide and reduced palladium thin films as hydrogen sensors. The palladium oxide thin films were deposited on thermally oxidized Si substrates using a reactive direct current (DC) magnetron sputtering system. Considerable changes in the resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Only recently, H 2 gas sensing of pure PdO thin film with nano-sized cracks and nanoflakes has been reported. 10,11 However, no recovery has been observed for this sensor at room temperature. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In general, thin films of PdO are prepared either by reactive sputtering 12 or by oxidation of Pd metal.…”
Section: Introductionmentioning
confidence: 79%
“…Only recently, H 2 gas sensing of pure PdO thin film with nano-sized cracks and nanoflakes has been reported. 10,11 However, no recovery has been observed for this sensor at room temperature. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In general, thin films of PdO are prepared either by reactive sputtering 12 or by oxidation of Pd metal.…”
Section: Introductionmentioning
confidence: 79%
“…In comparison to other metals, palladium shows the highest catalytic activity for hydrocarbons and carbon monoxide oxidation [26]. A number of research groups suggested PdO is the active phase in the process of catalytic combustion [7,12,27,28]. In the region of low temperature, PdO has stable chemical properties and high thermal stability [12,26].…”
Section: Discussionmentioning
confidence: 99%
“…The current density in the electrolytic cell was 0.7 mA cm −2 . The Ag/Pd film composition was changed as a result of chemical reaction PdO + H → Pd + H 2 O . Furthermore, during the hydrogenation the chemical reaction PbO + H → Pb + H 2 O, in which Pb reduces from amorphous PbO (from the structural component of the initial paste), can occur.…”
Section: Methodsmentioning
confidence: 99%